Species Composition of Fruit Flies (Diptera: Tephritidae) on Selected Fruit Crops in Northeastern Ethiopia - Aderajew Mihretie; Yitbarek Weldehawariat; Merkuz Abera (Psyche: A Journal of Entomology)
A study was conducted to characterize the species composition of fruit flies in South Wollo and North Wollo administrative zones of northeastern Ethiopia. Fruit flies were collected using two methods: rearing from infested mango, guava, and sweet orange fruits and trapping the adults with male lures and food-based attractants. Three fruit fly species were recovered from the fruits collected: Bactrocera dorsalis, Ceratitis cosyra, and Ceratitis capitata; in addition to these species, Ceratitis fasciventris was trapped. Bactrocera dorsalis was the most abundant species and accounted for 97.9 and 78.89% of the total trapped and emerged adults, respectively. The number of B. dorsalis and C. capitata showed a significant difference among trapping locations and attractants. The highest number of B. dorsalis was trapped with methyl eugenol at Kalu (722.2 flies per trap per week). Among the indigenous fruit fly species, C. capitata was higher at Habru which was guava and coffee-dominated habitat, whereas C. cosyra was relatively higher at Kobo which is mango dominated. More adults were trapped in male lure traps (97.03%) than in food-based attractants (2.97%). Hence, fruit fly management should focus on guava and mango crops which host all the fruit fly species, including the dominant B. dorsalis.